2021
DOI: 10.15251/cl.2021.1812.777
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of liquid-phase exfoliated gallium selenide flakes

Abstract: In this work, the photocatalytic activity of layered GaSe flakes obtained by liquid-phase exfoliation of bulk crystals was tested on the photodegradation of an organic dye under UV irradiation. The initial bulk GaSe crystals were synthesized by stoichiometric fusion method. Investigation of the structure and composition showed that as-grown crystal corresponds to β-polytype of GaSe. Analysis of the kinetics of the decomposition MB molecules showed that the obtained flakes demonstrate good photocatalytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, zinc oxide is susceptible to photocorrosion in aqueous and acidic electrolytes and dissolves to form Zn(OH) 2 [ 13 ]. Despite this limitation, experimental results have shown that ZnO actually exhibits higher photocatalytic activity than TiO 2 and other semiconductor catalysts, such as CdS, WO 3 , Fe 2 O 3 , SnO 2 , ZrO 2 , and GaSe [ 14 ], especially in the degradation of dyes in aqueous solution [ 15 , 16 , 17 , 18 , 19 ]. These advantages make it a good candidate for a photoelectrode in photoelectrochemical cells for water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…However, zinc oxide is susceptible to photocorrosion in aqueous and acidic electrolytes and dissolves to form Zn(OH) 2 [ 13 ]. Despite this limitation, experimental results have shown that ZnO actually exhibits higher photocatalytic activity than TiO 2 and other semiconductor catalysts, such as CdS, WO 3 , Fe 2 O 3 , SnO 2 , ZrO 2 , and GaSe [ 14 ], especially in the degradation of dyes in aqueous solution [ 15 , 16 , 17 , 18 , 19 ]. These advantages make it a good candidate for a photoelectrode in photoelectrochemical cells for water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the positions of the valence band (VB) and conduction band (CB) in a semiconductor material are main issue in terms of their energy levels relative to a reference electrode [1][2][3][4]. Tungsten oxide (WO 3 ) and its nanocomposites are actively used as photoactive nanomaterials in applications involving photoelectrochemical cells (PECs) [5][6][7]. This is due to their outstanding characteristics including photostability, a high electron mobility of approximately ~12 cm 2 V −1 s −1 , and extensive hole-diffusion length of about ~150 nm, the ability to absorb around of ~12% visible light, and cost-effectiveness [8].…”
Section: Introductionmentioning
confidence: 99%